ChemInform Abstract: One‐Pot Three‐Component Synthesis of Hantzsch 1, 4‐Dihydropyridines Promoted by Dimethyl Phosphate Ionic Liquids. Issue 1 (17th December 2015) - Priede, Elina; Zicmanis, Andris
Abstract: An unprecedented, convenient synthesis of a variety of 1, 4‐dihydropyridine derivatives is described using ionic ligands possessing a (Me‐O)2 PO2 ‐ counterion as promoter.